Development of a Role-Playing Model in the Material of Indonesia's Struggle for Independence History - Wiwid Nur Sulistiani; Eka Yusnaldi (MASI Mandiri Edukasi, 2026)
Social Studies (IPS) learning, particularly the material on Indonesia's Struggle for Independence, plays an important role in fostering historical awareness, nationalism, and students' character. However, IPS learning in Madrasah Tsanawiyah still tends to be teacher-centred and rote, thereby involving students less actively and not yet fully internalising the values of the struggle. This study aims to develop a role-playing learning model integrated with the Integrated IPS textbook on the History of Indonesia's Struggle for Independence for grade IX students at MTs Yanbu'ul Ulum Kandis, and to test its feasibility and effectiveness. This study uses a Research and Development (R&D) approach with stages including preliminary study, planning, product development, expert validation, limited trials, and model refinement. Data collection techniques include observation, interviews, learning outcomes tests, questionnaires, and documentation. The research results indicate that the developed role-playing learning model is valid and feasible, as assessed by material experts, learning model experts, and practitioners. In addition, the implementation of the model has been proven effective in improving cognitive learning outcomes, learning activities, nationalism attitudes, social skills, and students' learning motivation, as well as facilitating teachers in managing learning. Therefore, the role-playing learning model based on the Integrated Social Studies (IPS) textbook can serve as an innovative alternative for teaching history-related IPS in Madrasah Tsanawiyah, fostering more meaningful, contextual, and character-oriented learning.